“EXPLORING THE GUT-BONE AXIS: IMPACT OF GUT MICROBIOTA DYSBIOSIS AND DIETARY INTERVENTIONS ON BONE HEALTH” - Hafiz Hamad Farooq; Tausif Ahmad; Jawayria Qamar; Amama Zafar; Tayyaba Tariq; Waseem Dad Khan; Ayesha Adil; Sehrish Kanwal (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Osteoporosis is a prevalent global health issue characterized by bone fragility and an increased risk of fractures. Dysbiosis of the gut microbiota, marked by an imbalance in microbial communities, has emerged as a potential contributor to impaired bone health. Age, diet, and disease influence gut microbiota composition, disrupting bone metabolism signalling pathways, impairing calcium absorption, and dysregulating osteoclast activity, ultimately impacting bone strength and quality. This paper examines the intricate relationship between the gut microbiota and bone health, highlighting the role of dysbiosis in promoting osteoporosis and related disorders. Gastrectomy, neuropeptide secretion, and bacterial variance exacerbate bone loss by influencing calcium metabolism and systemic inflammation. The gut-bone axis, governed by interactions between gut physiology and microbial populations, is crucial in regulating bone metabolism. Dietary interventions, particularly involving prebiotics such as galactooligosaccharides (GOSs) and fructooligosaccharides (FOSs), promote bone health by modulating the gut microbiota. These prebiotics stimulate beneficial bacteria growth, enhance osteoblast activity, and improve calcium absorption and mineralization. Clinical trials in postmenopausal women and animal studies demonstrate the beneficial effects of prebiotic supplementation on bone density and turnover markers. Furthermore, randomized controlled trials and animal studies reveal that supplementation with calcium plus short-chain fructooligosaccharides (CaFOS) or fructooligosaccharides (FOS) increases femoral bone area and calcium content, reduces bone resorption, and decreases inflammation. These findings underscore the potential of dietary interventions targeting the gut microbiota to mitigate bone loss and prevent osteoporosis.